Report of deimatic display by Donacobius atricapilla (Linnaeus, 1766) (Passeriformes: Donacobiidae) - Morais, Luis Aguiar de (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
An unusual display behavior in response to the human approximation is reported for the Black-capped Donacobius, Donacobius atricapilla (Linnaeus, 1766). The observed bird showed a body size maximization display keeping static. The registered display is supposed to be a territorial response used to deter interspecific intruders.